KONSEP PEMBANGUNAN PARIWISATA BERKELANJUTAN (KASUS : DAMPAK PEMBANGUNAN PARIWISATA DI DESA JATILUWIH KECAMATAN PENEBEL KABUPATEN TABANAN) - Hadi Sukarno, Teguh (JURNAL KEPARIWISATAAN, 2017)
The purpose of this article is to identify the impact of tourism development in the Jatiluwih village. Sustainable tourism development needs the wise plan in involving the local people to participate how to manage the nature, build the tourism facilities with the consideration to conserve the local people socio cultural potencies in the toutism destination. Generally some resources has been made for tourist in the tourism destinations which has been used by local people for daily life. The result of research was found through observation which is combined with Typologi Public Participation concept, Basis of Sustainable Torism Development Theoty and Democracy Based Tourism Development Theory.